1989
DOI: 10.1097/00001888-198904000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Medical studentsʼ perceptions of cheating

Abstract: In 1985, 683 students at a large private upper-midwestern medical school were surveyed concerning the appropriateness of traditional cheating behaviors and behaviors related to professional misconduct and dishonesty in patient care. They also rated the acceptability of various rationalizations for these behaviors. The students agreed that traditional forms of academic cheating are inappropriate, but they did not agree about the appropriateness of certain behaviors in the areas of patient care and professional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…A study of 683 American medical students also found that freshmen were more likely to view dishonest clinical behaviour, such as "writing that a physical examination finding was normal without checking the patient", as wrong compared to the senior students. 17 The reversal of the trend, seen in our study, as students reach year five may reflect a greater involvement in patient care, the proximity of starting work as a junior doctor, and the realisation that what they write will soon have implications for patients.…”
Section: Discussionmentioning
confidence: 65%
“…A study of 683 American medical students also found that freshmen were more likely to view dishonest clinical behaviour, such as "writing that a physical examination finding was normal without checking the patient", as wrong compared to the senior students. 17 The reversal of the trend, seen in our study, as students reach year five may reflect a greater involvement in patient care, the proximity of starting work as a junior doctor, and the realisation that what they write will soon have implications for patients.…”
Section: Discussionmentioning
confidence: 65%
“…Third, we used established instruments to measure burnout and mental health. Fourth, items assessing professional behaviors and beliefs were derived from the literature [32][33][34][35] and the MSATU. 42,43 Conclusions Our data show that positive mental health seems to be associated with enhanced professional behaviors and beliefs among U.S. medical students.…”
Section: Discussionmentioning
confidence: 99%
“…11 Items regarding professional conduct explored cheating and dishonest professional behaviors that had been reported in previous studies of medical students. [32][33][34][35] Altruistic professional beliefs were assessed by asking students to rate their levels of agreement with statements regarding physicians' responsibility to society derived from the Medical Students' Attitudes toward Providing Care for the Underserved (MSATU) instrument. 34,35 Consistent with previous reports, 11 responses to these items were dichotomized to "agree" (responses of "strongly agree" or "agree") or "neutral/ disagree" (responses of "neutral," "disagree," or "strongly disagree") for analysis.…”
Section: Professional Behaviors and Beliefsmentioning
confidence: 99%
“…3 On a limited evidence base, cheating among medical students appears to be neither new nor confined to particular cultures, [3][4][5][6][7][8][9][10] although the introduction of information technology, cultural norms 3 7 and mismatches between student and faculty perceptions 11 have been claimed as contributory. In the main, reports either describe specific incidents 9 10 or depend on self-reported data from questionnaire surveys that reflect student experience and intention.…”
mentioning
confidence: 99%
“…In the main, reports either describe specific incidents 9 10 or depend on self-reported data from questionnaire surveys that reflect student experience and intention. [5][6][7][8] In some studies, the frequency of observations of cheating, or intentions to cheat, increased with seniority, suggesting that increasing experience of medical school is accompanied by the development of more relaxed peer norms towards academic misconduct. [6][7][8] In 2000, the BMJ reported the management of a student caught cheating during a clinical finals examination at a London medical school.…”
mentioning
confidence: 99%